2017
DOI: 10.1017/s1751731116002469
|View full text |Cite
|
Sign up to set email alerts
|

Review: Feeding conserved forage to horses: recent advances and recommendations

Abstract: The horse is a non-ruminant herbivore adapted to eating plant-fibre or forage-based diets. Some horses are stabled for most or the majority of the day with limited or no access to fresh pasture and are fed preserved forage typically as hay or haylage and sometimes silage. This raises questions with respect to the quality and suitability of these preserved forages (considering production, nutritional content, digestibility as well as hygiene) and required quantities. Especially for performance horses, forage is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
1
6

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 41 publications
(9 reference statements)
1
106
1
6
Order By: Relevance
“…Therefore, it is possible that the +SFD treated alfalfa still contained considerable levels of crude protein. Alternatively, it may be that the inclusion of a highfibre substrate negated the deleterious effects of the starch/inulin as it is well known that fibre is required to maintain gastrointestinal health in equids Harris et al, 2016;Julliand et al, 2001); therefore, it is possible that other fibrous feedstuffs may have had the same effects seen with the HTDA, an area that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that the +SFD treated alfalfa still contained considerable levels of crude protein. Alternatively, it may be that the inclusion of a highfibre substrate negated the deleterious effects of the starch/inulin as it is well known that fibre is required to maintain gastrointestinal health in equids Harris et al, 2016;Julliand et al, 2001); therefore, it is possible that other fibrous feedstuffs may have had the same effects seen with the HTDA, an area that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Diets high in fibre are required for normal gastrointestinal function in horses (Harris et al, 2016). Meanwhile, diets high in non-structural carbohydrates (NSC), such as starch and fructan, are known to elicit microbial disturbances often leading to clinical disorders like laminitis and colic (Hudson et al, 2001;Bailey et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Haylage has previously been defined as anaerobically stored forage containing 400-600 g DM per kg (Finner, 1966;Gordon, Derbyshire, Wiseman, Kane, & Melin, 1961;Greenhill, 1964). In more recent literature, haylage has been defined as wrapped or anaerobically stored forage containing >500 g DM per kg (Müller, 2005) and the same definition of haylage was used in a recently published consensus statement on feeding conserved forages to horses (Harris et al, 2017).…”
Section: Defin Ing Silage An D Haylagementioning
confidence: 99%
“…Recently, Harris et al () suggested that the minimum quantity of DM given as forage should be 12.5 g DM/kg BW, justifying it with health and ethological aspects related to the horse's needs. However, this minimum quantity was intended for a healthy horse, and may not be suitable for a post‐surgical recovering patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Harris et al (2017) suggested that the minimum quantity of DM given as forage should be 12.5 g DM/kg BW, justifying it with health and ethological aspects related to the horse's needs.…”
Section: Length Of Recovery (In Days)mentioning
confidence: 99%